Association between Hospitalist Productivity Payments and High‐Value Care Culture. Issue 1 (31st October 2018) - Gupta, Reshma; Steers, Neil; Moriates, Christopher; Ong, Michael
Abstract : BACKGROUND: Given the national emphasis on affordability, healthcare systems expect that their clinicians are motivated to provide high‐value care. However, some hospitalists are reimbursed with productivity bonuses and little is known about the effects of these reimbursements on the local culture of high‐value care delivery. OBJECTIVE: To evaluate if hospitalist reimbursement models are associated with high‐value culture in university, community, and safety‐net hospitals. DESIGN, PATIENTS, AND SETTINGS: Internal medicine hospitalists from 12 hospitals across California completed a cross‐sectional survey assessing their perceptions of high‐value care culture within their institutions. Sites represented university, community, and safety‐net centers with different performances as reflected by the Centers of Medicare and Medicaid Service's Value‐based Purchasing (VBP) scores. MEASUREMENT: Demographic characteristics and High‐Value Care Culture Survey (HVCCS™) scores were evaluated using descriptive statistics, and associations were assessed through multilevel linear regression. RESULTS: Of the 255 hospitalists surveyed, 147 (57.6%) worked in university hospitals, 85 (33.3%) in community hospitals, and 23 (9.0%) in safety‐net hospitals. Across all 12 sites, 166 (65.1%) hospitalists reported payment with salary or wages, and 77 (30.2%) with salary plus productivity adjustments. The mean HVCCS score was 50.2 (SD 13.6) on a 0‐100 scale. Hospitalists reported lower mean HVCCS scores if they reported payment with salary plus productivity (β = ‐6.2, 95% CI ‐9.9 to ‐2.5) than if they reported payment with salary or wages. CONCLUSIONS: Hospitalists paid with salary plus productivity reported lower high‐value care culture scores for their institutions than those paid with salary or wages. High‐value care culture and clinician reimbursement schemes are potential targets of strategies for improving quality outcomes at low cost.